Transcutaneous auricular vagus nerve stimulation improves cognitive decline by alleviating intradialytic cerebral hypoxia in hemodialysis patients: A fNIRS pilot study - Meng-Huan Wang; Yi-Jie Jin; Meng-Fei He; An-Nan Zhou; Mei-Ling Zhu; Feng Lin; Wen-Wen Li; Zhong-Li Jiang (Heliyon, 2024)
Cognitive impairment is common in hemodialysis patients, possibly due to inadequate cerebral blood flow during hemodialysis. No effective non-pharmacological interventions are available. This study investigates the impact of hemodialysis-induced cerebral hypoxia on cognitive decline in hemodialysis patients and the potential of transcutaneous auricular vagus nerve stimulation (taVNS) as a non-pharmacological intervention. A randomized controlled trial with 36 participants showed that cognitive performance and cerebral oxygenation in the dorsolateral prefrontal cortex (DLPFC) significantly declined in the sham group. In contrast, taVNS improved cognitive function by increasing cerebral oxygenation, with significant correlations to reaction times and MoCA scores. The study suggests that Hemodialysis-induced cerebral hypoxia may contribute to persistent cognitive decline in MHD patients. However, taVNS could be an effective intervention to prevent cognitive impairment in hemodialysis patients by alleviating cerebral hypoxia.